Toddlers’ Eating Behavior in Slum Urban and Semi Urban Communities: Study in Kampung Melayu and Bantul, Indonesia - Martha, Evi; Amelia, Tiara; ., Myranti (KnE Life Sciences, 2018)
ABSTRACT: Toddlers’ eating behavior is influenced by many factors. This study aimed to determine food consumption behavior of toddlers in the urban slum (Kampung Melayu) and semi urban slum (Bantul). The study used the Rapid Assessment Procedure qualitative approach. The informants were mothers or toddler sitters, health workers, and local community leaders. The results showed that in slum urban areas, there was a tendency for parents to give children options to decide for themselves how much and what foods they wanted. In addition, this condition was supported by habits of mothers who did not cook because of the narrow space at their home, therefore buying ready-to-eat food was practice, easier and relatively cheaper. In semi urban areas, mothers still cooked at home and occasionally bought food outside. However, the main reasons for cooking were efficiency, to reduce the use of flavorings and preservatives, as well as to control food hygiene. Milk was a complementary and given to children aged under three years. Eating in the dining room and at the dinner table was not a necessity due to space limitation in the slum urban area.